Service Quality, Patient Satisfaction, and Improvement Indicators - Mabini Jr., Silvestre P.; Narsico, Lalaine O.; Narsico, Peter G. (Future Science / FSH-PH Publications, 2024)
The study delves into the intricate symbiotic relationship between service providers and customers, which becomes increasingly complex amid competitive landscapes. It counts on the service provider’s capability to deliver exceptional service that fosters a unique customer satisfaction that not only encourages repeat patronage but also prompts referrals to others. The study sought to determine the presence of a correlation between the quality of service delivered by medical staff and patients' satisfaction levels by using the SERVQUAL model with 22 slightly modified indicators spread across five service quality dimensions that include reliability, assurance, tangibles, empathy, and responsiveness. The research was conducted within the confines of a hospital in Cebu. 314 patisents consented to participate in the data collection process. A survey was conducted to gather data on service delivery and another was conducted for patient satisfaction. Multiple regression analysis and Dublin-Watson test were used to compute correlations and Analysis of Variance (ANOVA) was used to compute the significance of difference. The following items are the findings. The five dimensions of service quality are above average and the service quality rating in its entirety was 3.756. Patient satisfaction was above average with a rating of 3.131. All the service quality dimensions were statistically correlated with patient satisfaction. Service quality in its entirety was statically correlated with patient satisfaction. There was a significant difference between service quality in its entirety and patient satisfaction. Finally, the ratings suggest that improvements were needed in all service dimensions, and because of high patient expectations improvements are both necessary and urgent.